Modul pembinaan karakter islami pada pendidikan anak usia dini - Shoumi, Ismi Izzatul; Alim, Akhmad (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the needs, design, and test the feasibility of developing an Islamic character development module specifically designed for implementation in Early Childhood Education (PAUD) units. This study used the Research and Development (R&D) method with the ADDIE development model. The results of the research in the needs analysis stage showed that 100% of PAUD teachers stated that the development of an Islamic character development module in Early Childhood Education is very much needed in schools. The results of validation tests by material experts, language experts, and media experts, as well as user assessments, indicate that the developed module is feasible and effective for use as teaching materials in Islamic character development. A module is considered possible if the assessment results meet, namely, with a feasibility percentage ≤ 61%. The feasibility test results for the Islamic Character Development Module in Early Childhood Education (PAUD) achieved a minimum and maximum score of 71.7%. The overall average score was 85.2%. Therefore, it can be said that this module is